2005
DOI: 10.1007/s00381-004-1106-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgically amenable epilepsies in children and adolescents: clinical, imaging, electrophysiological, and post-surgical outcome data

Abstract: Post-surgical seizure control in the pediatric population is similar to that in adult patients, despite the fact that epilepsies in this age group are more frequently of extratemporal origin, suggesting that surgery should be considered in children as soon as intractability is determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
22
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
11
22
0
2
Order By: Relevance
“…There was no difference in number of seizure-free patients between those with symptomatic and cryptogenic/idiopathic etiologies. This finding confirms that brain imaging with good resolution performed in patients with intractable seizures may be able to disclose the etiology, which would lead to specific treatment for seizure control [24,28].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…There was no difference in number of seizure-free patients between those with symptomatic and cryptogenic/idiopathic etiologies. This finding confirms that brain imaging with good resolution performed in patients with intractable seizures may be able to disclose the etiology, which would lead to specific treatment for seizure control [24,28].…”
Section: Discussionsupporting
confidence: 78%
“…Early surgical treatment has been recommended if it is feasible, in consideration of the possible neuronal damage from prolonged and repeated seizures, risk of adverse effects of multiple antiepileptic drug regimens, risk from injury during seizure recurrence and neuropsychological comorbidities [22,23]. For those who had distinct etiologies of epilepsy such as brain tumor and vascular malformation, surgical treatment had been considered as the definitive method of treatment with high expectation of seizure control [24]. Children who had intractable complex partial seizures, which are typical presentations of seizures of temporal lobe origin along with suspected mesial temporal sclerosis, are good candidates for surgical treatment with favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study group the most common etiology was MCD as previously reported elsewhere (3,6,10,12). Other most common etiologies were tumors, HS and gliosis.…”
Section: Discussionsupporting
confidence: 68%
“…Other most common etiologies were tumors, HS and gliosis. MCD and tumors predominate under 12 years but in patients over 12 years HS is more commonly observed, likewise in other series (10). Five patients had both MCD and HS in pathological specimens which are classified as dual pathology.…”
Section: Discussionmentioning
confidence: 52%